2015
DOI: 10.1002/2015gl063944
|View full text |Cite
|
Sign up to set email alerts
|

A self‐similar scaling for cross‐shelf exchange driven by transient rip currents

Abstract: Transient rip currents, episodic offshore flows from the surf zone to the inner shelf, present a recreational beach hazard and exchange material across the nearshore ocean. The magnitude and offshore extent of transient rip‐current‐induced exchange and its relative importance to other inner shelf exchange processes are poorly understood. Here 120 model simulations with random, normally incident, directionally spread waves spanning a range of beach slopes and wave conditions show that the transient rip current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 56 publications
6
65
0
Order By: Relevance
“…For instance, topographic rips can flow against permanent topographic features such as headlands or coastal structures (Pattiaratchi et al 2009;Castelle and Coco 2013;Scott et al 2016), flash rips are transient in both time and space (e.g. Ozkan- Haller and Kirby 1999;Feddersen 2014;Suanda and Feddersen 2015), and some rip currents can also be enforced by offshore bathymetric anomalies (Long and Ozkan-Haller 2005;Castelle et al 2012). These studies showed unique flow behaviours, suggesting that safety outcomes may contrast with what has been found for existing studies on rip current escape strategies on rip-channelled beaches.…”
Section: Assessment Of Rip Current Escape Strategies: Implications Fomentioning
confidence: 89%
“…For instance, topographic rips can flow against permanent topographic features such as headlands or coastal structures (Pattiaratchi et al 2009;Castelle and Coco 2013;Scott et al 2016), flash rips are transient in both time and space (e.g. Ozkan- Haller and Kirby 1999;Feddersen 2014;Suanda and Feddersen 2015), and some rip currents can also be enforced by offshore bathymetric anomalies (Long and Ozkan-Haller 2005;Castelle et al 2012). These studies showed unique flow behaviours, suggesting that safety outcomes may contrast with what has been found for existing studies on rip current escape strategies on rip-channelled beaches.…”
Section: Assessment Of Rip Current Escape Strategies: Implications Fomentioning
confidence: 89%
“…Similarly, other potential exchange mechanisms such as winds [e.g., Fewings et al, 2008], tides [e.g., Lentz and Fewings, 2012], or internal waves [e.g., Sinnett and Feddersen, 2014;Suanda et al, 2014] are expected to generally have much larger alongshore length scales and longer time scales than those observed. Farther offshore of the surfzone, Stokes-drift-driven exchange [e.g., Lentz et al, 2008;Suanda and Feddersen, 2015] or other inner-shelf processes may become important. The above differences in exchange velocity magnitude, vertical structure, and time and alongshore length scales indicate that on this day with moderate waves, the observed surfzone to inner-shelf cross-shore dye transport is dominated by rip current ejections.…”
Section: Surfzone/inner-shelf Exchange Mechanismsmentioning
confidence: 99%
“…The observed ejection events are episodic and brief (O(1) min) and occur at random alongshore locations, indicating that these rips are transient and are not bathymetrically controlled, consistent with the approximately alongshore-uniform bathymetry at Imperial Beach (Figure 1). The magnitudes of u à and T x SZ=IS are related to the surfzone eddy field and the frequency and intensity of these transient rip current events, which depend on the incident wave field and beach slope [Johnson and Pattiaratchi, 2006;Suanda and Feddersen, 2015].…”
Section: Surfzone/inner-shelf Exchange Mechanismsmentioning
confidence: 99%
“…). Reflective beaches are at the other extreme and are characterized by narrow surf zones, steep shore slopes, coarse sand if a beach and an absence of bathymetrically controlled rip currents, although transient rip currents can be present (Wright and Short , Suanda and Feddersen , Hally‐Rosendahl and Feddersen ). Transient rip currents form in all surf zones.…”
Section: Introductionmentioning
confidence: 99%
“…At sites without bathymetric rip currents, transient rip currents act like large patches of turbulence, which can eject water from the surf zone (Hally‐Rosendahl et al. , Suanda and Feddersen , Hally‐Rosendahl and Feddersen ). To compensate for this loss of water, water must enter the surf zone; transient rip currents cause the exchange of surf zone water with offshore water.…”
Section: Introductionmentioning
confidence: 99%